TRANSFORMATION OF PHOSPHOROUS IN GYPSIFEROUS SOILS AS AFFECTED BY DIFFERENT FERTILIZERS, LAND USE AND INCUBATION PERIODS - F. A. Hashim; K. A. Hassan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was investigated the P transformation in three soils gathered from different locations (Agricultural researches center in Tel Afar, Ain-Talawi and Sinu in Singar) in north of Iraq representing different gypsum content and land use [wheat (W), vegetable (V), uncultivated (Un)] after incubation period of (0, 5, 10, 30, 60, and 90) days. The soils were treated with 200 mg P kg-1 as superphosphate (S) or 30 g kg-1 soil manure as a cattle manure (A) or compost (p). The appropriate amounts of water were added to bring soil to estimated field capacity. After the specified time of each incubation period, sub-sample of soil analyzed for P, pH, EC and Ca. The results showed that P status affected by amendments and incubation periods. The soil which has more available P was the soil which treated with cattle manure. Generally, P was more available under (V) use compared to (W) use. After 90 days of incubation P solubility generally was higher than after 30 days. It appears from P solubility diagram that the best treatment was (A) which almost located between the two more soluble P compounds DCPD and DCP.